Pengaruh Pupuk N dan Cekaman Kekeringan terhadap Pertumbuhan dan Kandungan Artemisinin Tanaman Artemisia vulgaris L. - Elvina Sari; Zozy Aneloi Noli; Suwirmen Suwirmen (Universitas Andalas, 2018)
The research about effect of Nitrogen fertilizer and stress water on the growth and artemisinin content of Artemisia vulgaris L. has been conducted from December 2015 to March 2016 in Screen House and Plant Physiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Science, Andalas University, Padang. The purpose of this research were to the effect of Nitrogen fertilizer, stress water, and their interaction between on the growth and artemisinin content of A. vulgaris. This research used Completely Randomized Design (CRD) in factorial with four treatments ad three replications. The result showed that the number of leaves, plant height, length of roots, fresh weight, dry weight and of Artemisia vulgaris L. were increased significantly on N fertilizer treatments. The treatment of stress water 60% of volume capacity gave significantly effect on numbers of leaves and the highest content of Artemisinin was 80% volume capacity. The interaction of N fertilizer and stress water did not showed significantly effect on the growth and artemisinin content of Artemisia vulgaris L.